Cardiorespiratory fitness in volleyball athletes following a COVID-19 infection: A cross-sectional study - Milovancev, A.; Avakumovic, J.; Lakicevic, N.; Stajer, V.; Korovljev, D.; Todorovic, N.; Bianco, A.; Maksimovic, N.; Ostojic, S.; Drid, P. (International Journal of Environmental Research and Public Health, 2021)
Athletes` lifestyles have been dramatically affected by the coronavirus disease 2019 (COVID-19) pandemic. Since COVID-19 primarily affects the respiratory system and to a lesser degree the cardiovascular system, the goal of this study was to examine the effects of COVID-19-caused detraining on cardiorespiratory fitness (CRF) of recently recovered volleyball athletes. Sixteen experienced volleyball athletes (age 24 ± 4.5 years) who were recently diagnosed and recovered from a COVID-19 infection volunteered to participate in this study and were tested for CRF and spirometry. Given that participants had only mild symptoms of infection, the primary focus of this study was on the effects of detraining on CRF. On average, the time to exhaustion was 9.4 ± 1.4 min. VE, VCO2, RER and oxygen pulse increased, heart rate exceeded 90% of predicted values, and peak VO2 values were typical for this level of athlete (44.1 ± 3.4 mL/kg). Pulmonary function reflected in FVC, FEV1/FVC and MVV values were well above 80% of predicted values for each of the participants while electrocardiography revealed no ischemia, arrythmias or conduction and repolarization abnormalities were found in the tested subjects. Therefore, it can be concluded that participants experienced typical consequences of detraining. Due to a lack of CRF data prior to COVID-19 infection, we were unable to estimate the magnitude detraining had on CRF. Complete CRF assessment after COVID-19 infection in athletes can be useful for screening of residual myocardial and/or respiratory system damage for safe return-to-play decisions.